Mastering Autodesk Revit MEP 2011 - Bokmiller, Don (Autodesk official training guide., 2010)
"Master all the core concepts and functionality of Revit MEP. Revit MEP has finally come into its own, and this perfectly paced reference covers all the core concepts and functionality of this fast-growing mechanical, electrical, and plumbing software. The authors collate all their years of experience to develop this exhaustive tutorial that shows you how to design using a versatile model. You'll discover tips, tricks, and real-world exercises that only authors who use the software daily in a professional environment can know and explain. Explores the basics of the interface, how to create and use project templates, how to generate schedules that show quantities, materials, design dependencies, and more Examines the mechanical side of Revit MEP, including chapters on creating logical air, water, and fire protection systems and evaluating building loads Delves into how to best generate and model content, including solid modeling, creating symbols, using parameters, creating equipment, and more Featuring real-world sidebars, hands-on tutorials, and a supporting Web site, this reference allows you to jump into any tutorial and compare your finished work to the pros"--